Jerry Harvey: the quintessential life of sense and nonsense*. Issue 2 (3rd April 2017) - Dent, Eric B.
Abstract: The author pays homage to his former professor, the iconic, caring, profane, charming, and piercing Jerry B. Harvey. Harvey may have been the first person to teach a course on spirituality in a school of business. His work predated the establishment of the Management, Spirituality, and Religion interest group in the Academy of Management, dating at least to a talk about OD as a Religious Movement in 1964. The article is a critique of Harvey's œuvre in terms of work that was ahead of its time, work that is timely for today, work that is timeless, and work that feels dated at this point of the twenty-first century. In the final section, the author describes how Harvey's work impacted his career even several decades later.